Effect of source variation on the size and mixing state of black carbon aerosol in urban Beijing from 2013 to 2019: Implication on light absorption. (1st February 2021) - Wu, Yunfei; Xia, Yunjie; Zhou, Chang; Tian, Ping; Tao, Jun; Huang, Ru-Jin; Liu, Dantong; Wang, Xin; Xia, Xiangao; Han, Zhiwei; Zhang, Renjian
Abstract: Black carbon (BC) is the most important aerosol light-absorbing component, and its effect on radiation forcing is determined by its microphysical properties. In this study, two microphysical parameters of refractory BC (rBC), namely, size distribution and mixing state, in urban Beijing from 2013 to 2019 were investigated to understand the effects of source changes over the past years. The mass equivalent diameter of rBC ( D c ) exhibited bimodal lognormal distributions in all seasons, with the major modes accounting for most (>85%) of the rBC masses. The mass median diameter (MMD) was obviously larger in winter (209 nm) than in summer (167 nm) likely due to the contribution of more rBC with larger D c from solid fuel combustion and enhanced coagulation of rBC in polluted winter. More rBC particles were thickly coated in winter, with the number fraction of thickly coated rBC ( f coatBC ) ranging within 29%–48% compared with that of 12%–14% in summer. However, no evidential increase in BC light-absorption capability was observed in winter. This finding was likely related to the lower absorption efficiency of larger rBC in winter, which partly offset the coating-induced light enhancement. Two stage of decreases in MMD and f coatBC were observed, accompanied with a persistent decrease in rBC loading, thereby reflecting the discrepant effects of source control measures on rBC loading and physical properties. The control measures in the earlier stage before 2016 was more efficient to reduce the rBC loading but slightly influenced the microphysical properties of rBC. As of 2016, the reduction in rBC concentration slowed down because of its low atmospheric loading. However, rBC showed a more obvious decrease in its core size and became less coated. The decrease in f coatBC may have weakened the BC absorption and accelerated the decrease in light absorption resulting from the reduction in rBC loading. Graphical abstract: Image 1 Abstract : Decreases in BC core size and coating fraction were observed in Beijing from 2013 to 2019 in response to clean air actions.